Approximate calculation of the ground-state energy for Potts spin-glass models - Bittner, Elmar; Janke, Wolfhard; Saakian, David B. (Physical review. E, Statistical, nonlinear, and soft matter physics, 2003)
We consider the q-state Potts spin-glass model, with quenched couplings taking two different values only. As an approximation for this model a proper generalization of the random energy model is derived. Formulas of the resulting diluted generalized random energy model (DGREM) are applied to calculate the ground-state energy for the two-dimensional Potts spin-glass model. The semianalytical results are compared with numerical determinations of the ground-state energy, using multicanonical, random cost, and simulated annealing techniques.
Gesehen am 13.10.2022